Implications of erosion and bedrock composition on zircon fertility: Examples from South America and Western Australia. (15th May 2018) - Spencer, Christopher J.; Kirkland, Christopher L.; Roberts, Nicholas M. W.
Abstract: Isotopic analysis of zircon has been useful in charting our planet's geological history from the Holocene to the Hadean. Zircon is present in a range of lithologies, yet its yield in sedimentary systems is governed by the zircon fertility of the source rocks and their denudation rate. This interplay is illustrated in South America where rocks exposed in the Amazonia craton have higher Zr concentrations (i.e. greater zircon yield) than the Andes; however, the detrital zircon population of the Amazon River catchment shows more zircon from the Andes given the higher erosion rate. Nonetheless, the observed zircon frequency can be corrected for erosional and fertility biases. Additionally, detrital zircon in fluvial sediment in Western Australia, previously interpreted as quantifying differential erosion, can alternatively be explained as an effect of Zr content (therefore zircon fertility) of the sources. Understanding the variables controlling zircon yield will facilitate accurately interpreting detrital zircon signatures through deep time and their application to crustal evolution questions.